2020
DOI: 10.3390/jmse8110931
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Land–Sea Breeze System and the Surface Current Response in South-West Australia

Abstract: The land–sea breeze (LSB) system, driven by the thermal contrast between the land and the adjacent ocean is a widely known atmospheric phenomenon, which occurs in coastal regions globally. South-west Australia experiences a persistent and one of the strongest LSB systems globally with maximum wind speeds associated with the LSB system often exceeding 15 ms−1. In this paper, using field measurements and numerical simulations, we examine: (1) the local winds associated with the land–sea breeze with an emphasis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 74 publications
2
14
0
Order By: Relevance
“…The direction of the current vector anomaly is approximately 90° left to the wind direction (Figures 9a–9c). Previous studies on the LBS, particularly on the north of 30°N, where the inertial period is less than a day, showed that the current modulation with respect to diurnal wind forcing is as expected from classical Ekman drift theory (Fontán et al., 2013; Rafiq et al., 2020) in which the current is directed to the right of the winds. In our case, the inertial period is ∼2 days at the buoy location, which is much longer than the diurnal time scale of the LBS wind forcing.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The direction of the current vector anomaly is approximately 90° left to the wind direction (Figures 9a–9c). Previous studies on the LBS, particularly on the north of 30°N, where the inertial period is less than a day, showed that the current modulation with respect to diurnal wind forcing is as expected from classical Ekman drift theory (Fontán et al., 2013; Rafiq et al., 2020) in which the current is directed to the right of the winds. In our case, the inertial period is ∼2 days at the buoy location, which is much longer than the diurnal time scale of the LBS wind forcing.…”
Section: Resultsmentioning
confidence: 65%
“…However, a few studies have examined the impact of the LBS on different parts of the global ocean. Neetu et al (2006) studied the impact of the LBS on ocean surface waves over the eastern Arabian Sea and Rafiq et al (2020) studied the impact of the LBS on coastal currents of the southwestern Australian coast. Based on moored buoy observation in the Red Sea, Davis et al (2019) have shown that the LBS has the potential to modulate local air-sea interaction processes.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Surface current variability on the continental shelf within the study region is predominantly wind-driven (Fig. 2a; Smith et al 1991;Pattiaratchi et al 1997;Rafiq et al 2020). Southerly wind stresses overcome the alongshore pressure gradient during the summer months, moving upper layers offshore and favouring upwelling onto the continental shelf (Pearce and Pattiaratchi 1999).…”
Section: Study Regionmentioning
confidence: 99%
“…In this region, the diurnal tidal component has a maximum range of 0.60 m and the semidiurnal tide has a range of only 0.20 m [26]. There are three main wind regimes [27,28]: (1) calm winds (<5 ms −1 ); (2) strong winds associated with the passage frontal systems in winter with wind speeds >15 ms −1 with wind direction changing anti-clockwise from north to west to southwest; and (3) summer sea breezes (alike to a daily storm) with wind speeds >15 ms −1 blowing over 2-3 days from the south. Wind data from the Rottnest Island station over 2009-2016 indicated that the mean number of storms per year was 42 (range: 39-50) while 40% and 25% of the storms occurred during winter and summer months, respectively [27].…”
Section: Regional Settingmentioning
confidence: 99%